Losses in bifacial PERC solar cell due to rear grid design and scope of improvement. (August 2022) - Panda, Tamalika; Sadhukhan, Sourav; Acharya, Shiladitya; Chandra Mandal, Nabin; Nandi, Anupam; Bose, Sukanta; Das, Gourab; Mukhopadhyay, Sumita; Maity, Santanu; Chaudhuri, Partha; Saha, Hiranmay
Abstract: Photovoltaic (PV) industries are continuously trying to improve the module performance with the adoption of newer cell technologies. Recently, bifacial passivated emitter rear contact (PERC) solar cell technology has entered the market to further improve the module performance through the absorption of the extra photons reflected from the background. This work is mainly focused on optimizing the rear side grid pattern of the bifacial PERC solar cells for improvement of the total output power gain. We have developed an analytical model based on the front and rear grid pattern of commercially available bifacial PERC solar cells to calculate the optical shading and electrical losses for both sides of the solar cells. It is perceived that the rear shading loss due to rear grid design of industrial bifacial PERC solar cells is very high (∼30%) as compared to the front side (∼5%) of the cells. The model calculation shows that if with the improved laser scribing technology the finger width of the rear grid pattern be drastically reduced from ∼ 200 μm (measured value) to 25 μm the optical shading loss may be minimized to 11–14% from 30% without compromising the effective busbar resistance.